Risk management improvement in the sales phase of a global construction business to increase the profit of projects and business : Case study - Olli, Maria (My University, 2023)
This thesis studies the risk management improvement in the sales phase of an energy construction business and if risk management executed already at this phase can increase the financial business result through decreasing the negative margin deviation of the projects. The study is made from the constructor business perspective. The basis of the research method is an action study. The research question is how and what type of risk management should the global, case construction business implement in the project sales phase to have a meaningful, positive impact on the project cost overruns? The business result of the case company was heavily impacted at the end of 2019 by projects which were delivered with negative margin deviation. One of the root causes for the result was studied to be an inadequate risk identification and management at the sales phase. The theoretical part of the study analyses the concepts of project risk management in general, risk management specifically in the sales phase of projects and further the risk management in the construction business. In addition, it reviews the risk management tools as well as the concept of contingency reservations. Also, the concept of action research is defined and its relevance for this study is analyzed. The framework for the case action research is also defined. The practical part of the action research follows the planning and implementation of risk management process in the case company. The effect of the implemented risk management process is reviewed against the results on the project margin deviations. Results demonstrate that the described implementation of risk management in the sales phase of the case company was successful. The margin deviation summary report demonstrates the A class projects with implemented risk management practices in sales phase causing 66% less negative margin deviation in average than projects without risk management. This means that the case company could increase its profit by 66% having the risk management implemented for all the future A class projects.
Keywords: risk management; risks; projects; leadership (activity); business; development (active); energy management; action research; sales managers; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development